Are demonstration plots useful for learning & scaling the adoption of improved forages? - Sibiko, Kenneth W; Korir, Gilbert K.; Pazos Cardenas, M; Mwendia, Solomon W; Burkart, Stefan; Notenbaert, An Maria Omer (2024)
Within the Grass 2 Cash @Scale project, we established over 2,400 forage demonstration plots or farms across Kenya and Uganda. On each established plot the project provided at least three varieties of Brachiaria hybrids, Brachiaria cultivars, Panicum maximum, and (in some cases) forage legumes and trees. Initially, there was limited information on the location, current state, and utilization of these plots. This presentation provides descriptive results from a rapid survey conducted in 2024, detailing the current status, locations, and characteristics of host farmers and demonstration farms. It also covers variety preferences, the use of demonstration farms for learning and disseminating planting materials, gender dynamics, and the benefits of cultivated forages in enhancing feed availability, milk productivity, and household incomes.